How, when and why can the mother-tongue language be forgotten? The case of international adoption - Ramonaitė, Jogilė Teresa; Ramonienė, Meilutė (Taikomoji kalbotyra, 2021)
The present paper deals with the attrition of the first language. It presents a general overview of language attrition as a research field and discusses the main characteristics of the phenomenon by examining some typical lexical, grammatical, and phonological properties of attriters’ speech. Our attention is drawn here to a variety of factors, such as age, time spent in the L2 environment, frequency of first language use, language attitudes, and other aspects that have an impact on language attrition. The paper also reflects on and motivates the choice of the term ‘attrition’ in the Lithuanian academic use. The current empirical analysis focuses on an extreme case of first language attrition in the situation of international adoption of an early-teenager (~12 years old) Lithuanian girl adopted to Italy. The linguistic development of the girl was normal, and at the time of adoption she was regularly literate in Lithuanian L1. With the adoption, her language environment switched completely from Lithuanian to Italian. This case study is based on longitudinal observation and speech recordings mainly from the final stage of the observation period, i.e., 14 months after her departure from the country of origin. The paper examines Lithuanian utterances and other elements of the Lithuanian language in the girl’s communication. Her spontaneous speech is analysed mostly on the lexical and grammatical level, but some other language levels are also touched upon. The analysis shows a very advanced stage of first language attrition not only on the most evident – lexical – level, but also substantial changes on the grammatical level. The data shows that categories of tense, aspect, indefiniteness, case, and even gender, which differ in the two – Lithuanian and Italian – languages, have been impacted by the new dominant language. To conclude, even though the girl’s age and particularly positive attitudes towards the Lithuanian language were quite likely the most important factors for her maintaining some of the language one year later, the attrition of her L1 is still very advanced.
Keywords: language attrition; bilingualism; Lithuanian L1; vocabulary; grammar